Clinical significance of circulating tumor cells and tumor markers in the diagnosis of lung cancer. (27th May 2019) - Li, Yang; Tian, Xudong; Gao, Lei; Jiang, Xiaohong; Fu, Rao; Zhang, Tingting; Ren, Tianying; Hu, Ping; Wu, Yaping; Zhao, Peige; Yang, Dawei
Abstract: Background: Lung cancer has the highest fatality rate of all cancer types. To improve patients' survival and life quality, it is therefore very important to screen for and detect it at an early stage. Methods: A negative enrichment–fluorescence in situ hybridization (NE‐FISH) approach was used to detect circulating tumor cells (CTCs) in lung cancer patients, and levels of lung cancer‐associated serum markers were also measured in the peripheral blood of these same patients. The correlation between CTCs, serum cancer markers (carcinoembryonic antigen [CEA], CA 125, CYFRA 21‐1, and SCC), and clinicopathological characteristics was then investigated. Moreover, the potential clinical use of the combination of CTCs and tumor markers for the diagnosis of lung cancer, especially at early stages, was also explored. Results: CTC frequencies in lung cancer patients were significantly higher than in healthy control volunteers or patients with benign lung disease, and the area under the receiver operating characteristics curve for the control group was 0.846 (95% CI 0.796‐0.887, P  < 0.001). The rate of CTC positivity in lung cancer patients was 68.29% when the CTC cutoff value was 2, and the sensitivity of this means of lung cancer detection rose to 82.93% by combining CTC‐based detection with measurements of serum tumor markers. Similarly, the diagnostic sensitivity of this approach in early‐stage lung cancer patients (I‐II) was improved from 63.93% to 78.69%. Detection of CTCs can thus assist with the identification of benign and malignant pulmonary nodules. Conclusions: It is potentially helpful and effective to employ a combination of CTCs and serum tumor markers for the clinical diagnosis of lung cancer. Abstract : Circulating tumor cells (CTCs) and serum tumor markers were detected in lung cancer patients. CTCs detected in lung cancer patients were significantly higher than those of the control group and benign lung disease. The sensitivity of the means of lung cancer detection was 82.93% by combining this CTC‐based detection with serum tumor markers.